Estimation of Densities of Some Polymers Based on Bisphenol-A - Varada Rajulu, A. (Asian Journal of Chemistry, 2010)
The densities and the volume expansion coefficients of some polymers based on bisphenol–A have been estimated by group counting method. A close agreement between the estimated and experimental values has been observed.